Effect of Tile Powder Used as a Cementitious Material on the Mechanical Properties of Concrete - Bheel, N.; Abbasi, R. A.; Sohu, S.; Abbasi, S. A.; Abro, A. W.; Shaikh, Z. H. (Engineering, Technology & Applied Science Research, 2019)
This study was undertaken to reduce the usage of cement in concrete where different proportions of tile powder as cement replacement were used. Since in the manufacture of cement an exuberant amount of carbon dioxide is disposed of in the environment, this research aims to curtail the dependence on cement and its production. The objective of this work is to investigate the properties of fresh mix concrete (workability) and hardened concrete (compressive and splitting tensile strength) in concrete with different proportions of 0%, 10%, 20%, 30%, and 40% of tile powder as a cement substitute. In this study, a total of 90 concrete samples were cast with mix proportions of 1:1.5:3, 0.5 water-cement ratio, cured for 7, 14 and 28 days. For determining the compressive strength, cubical samples, with dimensions of 100mm×100mm×100mm, were cast, while for the determination of the splitting tensile strength, cylindrical samples with dimensions of 200mm diameter and 100mm height, were tested after 7, 14, and 28 days. The highest compressive strength of concrete achieved for tile powder concrete was 7.50% at 10% replacement after 28days of curing. The splitting tensile strength got to 10.2% when concrete was replaced with 10% of tile powder and cured for 28 days. It was also shown that with increasing percentage of the tile powder content, the workability of the fresh concrete increases.